THE IMPACT OF ENGLISH-SPEAKING CONTENT VIDEOS ON INSTAGRAM ON STUDENTS' SPEAKING SKILLS - Prayoga, Suhendri; Anastasia, Faurina; Feny Martina; Siregar, M. Riskiyadi (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2024)
Students' speaking skills can be enhanced by using Instagram English content videos as a teaching and learning tool. With Instagram, students can simultaneously practice four separate English language skills. Instagram offers the chance to participate in a dialogue process. Because Instagram is thought to be the best place for EFL learners to produce language exposure, it can therefore accommodate speaking practices. The purpose of this research is to determine whether Instagram's English-language content videos have a noteworthy impact on the speaking abilities of State Islamic University of Sultan Syarif Kasim Riau students. Ex post facto design and quantitative methodology were employed in this investigation. The researchers distributed the questionnaire in order to gather data. Which were choosen by using purposive sampling. On May 25, 2023, the Department of English Education at UIN SUSKA Riau hosted this research. the information gathered from 42 samples. They were English Education Department fourth-semester students. Furthermore, surveys were employed to collect the information. The results showed that students' speaking abilities are significantly impacted by Instagram English content videos, utilizing the simple linear regression computation table. The T ratio gain of 10.777 is higher than the T table value of 2.020, meaning that 10.777 > 2.020. Next, 0.00 was the significant value (0.00 < 0.05), which is less than 0.05. It is clear from this outcome that Ha is approved and Ho is refused. Thus, Instagram English content videos have an impact on students speaking skills.